2021
DOI: 10.1136/bmjopen-2020-047511
|View full text |Cite
|
Sign up to set email alerts
|

Health programmes and services addressing the prevention and management of infectious diseases in people who inject drugs in Canada: a systematic integrative review

Abstract: ObjectivesPeople who inject drugs (PWID) experience a high burden of injection drug use-related infectious disease and challenges in accessing adequate care. This study sought to identify programmes and services in Canada addressing the prevention and management of infectious disease in PWID.DesignThis study employed a systematic integrative review methodology. Electronic databases (PubMed, CINAHL and Web of Science Core Collection) and relevant websites were searched for literature published between 2008 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 114 publications
(79 reference statements)
2
7
0
Order By: Relevance
“…The evidence for THN is limited Inconclusive McDonald [ 47 ] SLR 22 observational studies (n = 2912) Any health setting THN • Overdose reversals: 96.3% [95.5–97.1] (n = 2249/2336 THN administrations) • Deaths: 0.9% [0.5–1.2] (n = 24/2336 THN administrations) Low-moderate THN programmes can reduce overdose mortality with a low rate of adverse events. However, there is a large variability in the size and quality studies Inconclusive Other combined interventions and interventions’ comparisons Bouzanis [ 48 ] SLR 97 interventional and observational studies Any health setting in Canada NSEP SCF/SIF OAT PoC Behavioral interventions Evidence indicates advantages of multifaceted care programmes for PWID, which include harm reduction, medical/pharmaceutical treatments, social support and education The included studies call for exploratory work in facilitators and barriers to treatment and care, more robust study designs, and attention to contextual factors and more complex interventions Inconclusive Cross [ 49 ] SLRMA 18 interventional studies (n = 7926) Any health setting Educational interventions NSEP • Risky behavior, educational studies : WM: 0.749 [0.708–0.790] • Risky behavior, NSEP studies: WM: 0.279 [0.207–0.352] Both interventions had a positive impact on reducing HIV risk behaviors, however, results are dependent upon research design, outcomes, follow-up Yes Hagan [ 50 ] SLRMA 26 interventional and observational studies Any health setting ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence for THN is limited Inconclusive McDonald [ 47 ] SLR 22 observational studies (n = 2912) Any health setting THN • Overdose reversals: 96.3% [95.5–97.1] (n = 2249/2336 THN administrations) • Deaths: 0.9% [0.5–1.2] (n = 24/2336 THN administrations) Low-moderate THN programmes can reduce overdose mortality with a low rate of adverse events. However, there is a large variability in the size and quality studies Inconclusive Other combined interventions and interventions’ comparisons Bouzanis [ 48 ] SLR 97 interventional and observational studies Any health setting in Canada NSEP SCF/SIF OAT PoC Behavioral interventions Evidence indicates advantages of multifaceted care programmes for PWID, which include harm reduction, medical/pharmaceutical treatments, social support and education The included studies call for exploratory work in facilitators and barriers to treatment and care, more robust study designs, and attention to contextual factors and more complex interventions Inconclusive Cross [ 49 ] SLRMA 18 interventional studies (n = 7926) Any health setting Educational interventions NSEP • Risky behavior, educational studies : WM: 0.749 [0.708–0.790] • Risky behavior, NSEP studies: WM: 0.279 [0.207–0.352] Both interventions had a positive impact on reducing HIV risk behaviors, however, results are dependent upon research design, outcomes, follow-up Yes Hagan [ 50 ] SLRMA 26 interventional and observational studies Any health setting ...…”
Section: Resultsmentioning
confidence: 99%
“…This evidence is further limited by the evaluation design and number of successful reversals. Only one systematic review without meta-analysis by Bouzanis et al [ 48 ] (critically low methodological quality) mentioned the use of point-of-care HIV/HCV testing and treatment interventions, such as integrated multidisciplinary HIV and HCV care, supportive housing models, and addiction treatments for this population. Results should be carefully approached given the limitations in primary studies, including lack of randomization, self-reported measurements, and challenges in data generalizability (i.e., experiences often specific to PWID).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The one-stop shop approach, an integrated care model combining multispecialised teams to gather all necessary competences on one site, can reduce the complexity of care pathways [ 22 ]. These interdisciplinary, integrated care structures consistently show positive effects on the health and wellbeing of PWID, including mental health outcomes [ 15 , 23 , 24 ], by reducing the risk of loss to follow-up when patients have to navigate through complicated standard healthcare pathways [ 25 ]. Our analysis shows that integrated approaches that included testing, medical supervision, peer counselling, social support and/or OAT provided on one site were of particular importance for increasing adherence to treatment (4/4 MoGPs) and also for optimising community-based testing (4/6 MoGPs).…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of PEs is however one of many strategies to reach out to PWID. Countries within Africa and globally have successfully applied community-based approaches to provide a variety of health services to PWID including, HIV and viral hepatitis testing, supervised injection facilities, needle exchange programs, and OST [ 40 , 41 ]. However, PE programs hold several advantages over community-based programs, including reduction of stigma and promotion of effective communication.…”
Section: Discussionmentioning
confidence: 99%